Technology mouse scanner / Nabihah Rozali...[et al.] - Rozali, Nabihah; Nizar, Nur Liyana; Ahmmed Aziz, Nursuriayana; Japri, Siti Nazira; Hassan @ Hassim, Suriya
Description of product concept The product to be developed is technology mouse scanner. The function of this product is to convert hard copy into soft copy with only the mouse. Besides, to save the hard copy directly to USB attached to the soft copy.